Perspectivas sustentáveis nas compras governamentais: um estudo de caso na Universidade Federal Rural da Amazônia - SILVA, Jayme Nascimento (Universidade Federal do Pará, 2019)
Laws of Sustainable Public Procurement provides for the adoption of sustainable criteria in government procurement by the Federal Public Administration. This type of shopping was established to stimulate sustainable development in the market, notably in public organizations. The Federal Rural University of Amazonia (UFRA) in the years 2011 and 2012 was assessed by external control agencies, by not adopting sustainable criteria in their purchases. Thus, the research presented here aims to propose the construction of a set of sustainability criteria, aiming at future deployment, for use in purchases UFRA. To achieve the objective set, describes the empirical environment of shopping in the institution and proposes a set of methods and techniques, among which the application of a survey line with the revised theories. As a theoretical basis addressed to concepts and theories that underlie sustainable development, leading to the logic of the use of state purchasing power, succeeding to the idea of Sustainable Public Procurement. Results obtained are presented and analyzed considering the principles for sustainable procurement. The conclusion of the research shows that the University is not using the full form sustainable criteria in their procurement processes, and that the servers have misconceptions of the concepts of shopping with sustainable character. It proposes a set of actions that will subsidize the use of sustainable criteria, combined in order to improve compliance with the institution's mission